Genetic architectures of ADME genes in five Eurasian admixed populations and implications for drug safety and efficacy. Issue 9 (29th July 2014) - Li, Jing; Lou, Haiyi; Yang, Xiong; Lu, Dongsheng; Li, Shilin; Jin, Li; Pan, Xinwei; Yang, Wenjun; Song, Manshu; Mamatyusupu, Dolikun; Xu, Shuhua
Abstract : Background: Drug absorption, distribution, metabolism and excretion (ADME) contribute to the high heterogeneity of drug responses in humans. However, the same standard for drug dosage has been applied to all populations in China although genetic differences in ADME genes are expected to exist in different ethnic groups. In particular, the ethnic minorities in northwestern China with substantial ancestry contribution from Western Eurasian people might violate such a single unified standard. Methods: In this study, we used Affymetrix SNP Array 6.0 to investigate the genetic diversity of 282 ADME genes in five northwestern Chinese minority populations, namely, Tajik, Uyghur, Kazakh, Kirgiz and Hui, and attempted to identify the highly differential SNPs and haplotypes and further explore their clinical implications. Results: We found that genetic diversity of many ADME genes in the five minority groups was substantially different from those in the Han Chinese population. For instance, we identified 10 functional SNPs with substantial allele frequency differences, 14 functional SNPs with highly different heterozygous states and eight genes with significant haplotype differences between these admixed minority populations and the Han Chinese population. We further confirmed that these differences mainly resulted from the European gene flow, that is, this gene flow increased the genetic diversity in the admixed populations. Conclusions: These results suggest that the ADME genes vary substantially among different Chinese ethnic groups. We suggest it could cause potential clinical risk if the same dosage of substances (eg, antitumour drugs) is used without considering population stratification.